1993
DOI: 10.1111/j.1532-5415.1993.tb02049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Testosterone Replacement Therapy in Old Hypogonadal Males: A Preliminary Study

Abstract: These preliminary findings support the need for long term studies of testosterone therapy in older hypogonadal males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
186
2
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(204 citation statements)
references
References 25 publications
11
186
2
5
Order By: Relevance
“…In most of these studies, the body weight change did not differ significantly. Testosterone therapy was associated with a greater improvement in grip strength than placebo [37,74,75]. A recent double-blind placebo-controlled study showed benefits of testosterone administration on skeletal muscle performance in elderly men with chronic heart failure [76], and another one found positive effects on the prevention of loss of muscle strength of the lower limbs [77].…”
Section: Muscle Mass and Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these studies, the body weight change did not differ significantly. Testosterone therapy was associated with a greater improvement in grip strength than placebo [37,74,75]. A recent double-blind placebo-controlled study showed benefits of testosterone administration on skeletal muscle performance in elderly men with chronic heart failure [76], and another one found positive effects on the prevention of loss of muscle strength of the lower limbs [77].…”
Section: Muscle Mass and Strengthmentioning
confidence: 99%
“…Long-term follow-up of testosterone replacement in hypogonadal males and a control group indicates that self-assessment of libido was significantly higher in the testosterone-treated group [50]. Testosterone replacement has also been shown to enhance libido and the frequency of sexual acts and sleep-related erections [75,89].…”
Section: Improved Sexual Desire Function and Performancementioning
confidence: 99%
“…Table 4 summarizes a number of studies demonstrating positive effects of testosterone replacement in men, similar to those seen with estrogen in women (25). In humans, testosterone increases muscle mass (26), muscle strength (27)(28)(29), bone mineral density (29,30), hemoglobin (28), and visuospatial cognitive function (31). Studies in the SAMP8 mouse, an animal model of Alzheimer disease (32), suggest that testosterone may play a role in the decline in memory and the overproduction of amyloid-6 protein seen in this species (14).…”
Section: The Hormonal Fountain Of Youthmentioning
confidence: 99%
“…There is some evidence suggestive of reduced bone turnover; testosterone enanthate 100 mg weekly for 3 months led to a reduction in urinary hydroxyproline excretion compared with placebo (Tenover, 1992), and testosterone enanthate 200 mg every 2 weeks for 3 months led to increased osteocalcin compared with untreated controls (Morley et al, 1993). Testosterone replacement has been associated with increased haematocrit (Tenover, 1992;Morley et al, 1993) which may be beneficial but rarely may also lead to problems with polycythaemia. The effect on lipids is probably minor, with reduction in cholesterol and low density lipoprotein (LDL), and a decline or no change in high density lipoprotein (HDL) (Tenover, 1992;Morley et al, 1993).…”
Section: Ageingmentioning
confidence: 99%
“…Testosterone replacement has been associated with increased haematocrit (Tenover, 1992;Morley et al, 1993) which may be beneficial but rarely may also lead to problems with polycythaemia. The effect on lipids is probably minor, with reduction in cholesterol and low density lipoprotein (LDL), and a decline or no change in high density lipoprotein (HDL) (Tenover, 1992;Morley et al, 1993). The resulting effects on the cardiovascular system have not been firmly established.…”
Section: Ageingmentioning
confidence: 99%